An Example of Symbiotic Relationships in La Guajira during the XVIII Century. The History of a Revolt under Chief Cecilio’s Leadership - Restrepo Olano, Margarita (Revista Complutense de Historia de América, 2013)
This article is about the leadership of Indian Chief Cecilio and his close relationship with the merchants of the Guajira region, some of which were peninsulares dedicated to contraband. These also joined forces against Lieutenant Governor Jose Javier Pestaña, the highest authority in the region, who, like other governors, wanted to gain control of those practices. This struggle stirred in a revolt against the lieutenant, which resulted in his fatality, and in which local merchants and even local authorities were found to be acting in connivance with Chief Cecilio. In the words of the Norwegian historian Steinar Saether, this outbreak of 1753 is an example of “complexity, flexibility and pragmatism”. In brief, these were symbiotic relationships.